DESIGN AND BUILD AN ANDROID-BASED CUSTOMER MENU RECORDER APPLICATION ON BENU COFFEE SHOOP USING AGILE METHODS - Putri, Wita Atika; Irwan, Dedy; Lubis, Husni (Bahasa Indonesia, 2024)
Information technology is a process from obtaining data to processing and analyzing the data so that it is stored in various ways to create or produce quality information. Currently, the development of information technology is very rapid and fast, including in Indonesia itself, therefore this research explores the Android-based design "Design and Build an Android-Based Customer Menu Recording Application at Benu Coffee Shop Using Agile Methods". Benu Coffee Shop, as a favorite place in the city center, faces challenges in the ordering system which still uses manual methods using pen and paper. Therefore, a system is needed that can manage menu orders according to customer and cafe needs. The Agile method was chosen for the development of this system because of its flexibility in adapting to changing needs. This research includes needs analysis, design of use case diagrams, activity diagrams, class diagrams, and databases. This system allows admins to manage menus, tables, customers and sales reports. System testing is carried out using the black-box method to ensure the expected functionality. Test results show success in displaying the login page, navigation and customer menu ordering. This system is expected to improve efficiency and service quality at Benu Coffee Shop by providing solutions that are responsive to changing needs.